Synthetic leverage and fund risk-taking - Daniel Fricke (Deutsche Bundesbank, 2021)
Mutual fund risk-taking via active portfolio rebalancing varies both in the cross- section and over time. In this paper, I show that the same is true for funds' off- balance sheet risk-taking, even after controlling for on-balance sheet activities. For this purpose, I propose a novel measure of synthetic leverage, which can be estimated based on publicly available information. In the empirical application, I show that German equity funds have increased their risk-taking via synthetic leverage from mid-2015 up until early 2019. In the cross-section, I find that synthetically leveraged funds tend to underperform and display higher levels of fragility.
Keywords: E44; G11; G23; 330; leverage; risk-taking; derivatives; securities lending; mutual funds